Increased serum interleukin-9 and interleukin-1β are associated with depression in type 2 diabetes patients - VARSHNEY, Prabhat; PARVEEN, Rizwana; KHAN, Mohd Ashif; KOHLI, Sunil; AGARWAL, Nidhi B. (Arquivos de Neuro-Psiquiatria, 2020)
Background: Co-morbid diabetes and depression are prevalent chronic conditions negatively affecting quality of life (QoL). Inflammation has been considered as an integral mechanism in patients with both diabetes and depression. Objective: The aim of the present study was to investigate depression and its association with interleukins (IL)-1β and IL-9 in type 2 diabetic patients (T2DM) and controls. The QoL in diabetic patient was also assessed. Methods: Eighty subjects were included, distributed among three groups: Group 1 - Healthy controls; Group 2 - T2DM patients without depression; Group 3 - T2DM patients with depression. Depression and QoL were assessed using Patient Health Questionnaire (PHQ-9) and The Audit of Diabetes-Dependent QoL (ADDQoL), respectively. IL-1β and IL-9 were measured in serum samples of all the patients using ELISA kit. Results: The PHQ score in the Group 3 was significantly higher as compared to Group 1. The ADDQoL scores in the Group 3 were significantly higher as compared to Group 2. Levels of IL-9 and IL-1β were elevated in Group 3, as compared to the other groups. Conclusion: This study showed positive association between depression and IL-1β, IL-9 in T2DM patients. Additionally, the diabetic patients have poorer quality of life, which is further worsened by the presence of depression. Thus, routine assessment for the presence of depression is suggested in T2DM patients.
Keywords: Cytokines; Depression; Patient Health Questionnaire